An ent-kaurene derivative from aerial parts of baccharis rufescens - Simirgiotis, Mario Juan (2003)
From aerial parts of Baccharis refescens Sprengel (Asteraceae: Astereae), the diterpene ent-3a,19-disuccinyloxy-kaur-16-ene (1) was isolated along with the triterpene oleanolic acid (4) and the flavonoids cirsimaritin (5,4'-dihidroxy-6,7-dimethoxyflavone) (5), and cirsiliol (5, 3',4'-trihidroxy-6,7-dimethoxyflavone) (6). Biological assays aimed to evaluate the incidence of compound 1 and its methyl ester derivative (2) on the food comsuption of adults of Tribolium castaneum (Herbst) (Coleoptera: Tenebrionidae), showed that compound 2 exhibited a significant antifeedant activity.